A Generational Shift: The military history crisis in the Estonian military education 1919–1940 - Kopõtin, Igor (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2019)
The article analyses the teaching of military history in the Estonian army in the interwar period. It argues that the basic concepts – the purpose, thematic distribution, teaching methods – were developed by the former professor of the tsarist military academy, Lt. Gen. Aleksei Baiov. Baiov stressed that history, along with strategy, was at the core of military science. However, Baiov and other Russian émigrés came under heavy criticism from the Estonian command, particularly Gen. Nikolai Reek, who thought Estonia was too small to require a school of strategy. In the background, there was the theoretical clash, carried over from the pre-war tsarist Russia, between the old generation of bayonet tac- tics and the new generation of fire and movement. In 1926, Baiov was fired, but Reek’s reforms, which subordinated history to the needs of tactical training, remained incomplete even at the end of the 1930s. A number of questions about the utility and the substance of military his- tory remained unresolved. Indeed, they are still not settled in Estonian officer education today.